Content Analysis of Social Studies Textbooks of Primary School Regarding Indices of Changes in Believes, Behaviors and Attitudes which are Starting Point of Development - Mohammad Bagher Beheshti; Karim Mahmoodi; Fatemeh Hosseinpoor (توسعه اجتماعی, 2017)
Economic growth or programs oriented toward it cannot guarantee development of societies alone. To reach development, changes in believes, behaviors and attitudes are prior to such programs. Since school textbooks are suitable tools for offering changes in believes, behaviors and attitudes, this study is to content analyze social studies textbooks of primary school during the educational year of 2015-2016 regarding such kind of indices. The research data suggested that among indices of changes in believes, behaviors and attitudes studied textbooks paid more attention to “collectivism or socialization”, “scientism”, “social discipline”, and “attachment to the country”. While other indices i.e. “work ethics and loyalty”, “social trust”, “punctuality”, and “respecting the right of others” attracted attention less than expected.